2018
DOI: 10.4012/dmj.2017-078
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties of discontinuous S2-glass fiber reinforced resin composite

Abstract: The objective of this study was to investigate several physicochemical properties of an experimental discontinuous S2-glass fiberreinforced resin composite. The experimental composite was prepared by mixing 10 wt% of discontinuous S2-glass fibers with 27.5 wt% of resin matrix and 62.5 wt% of particulate fillers. Flexural strength (FS) and modulus (FM), fracture toughness (FT), work of fracture (WOF), double bond conversion (DC), Vickers hardness, volume shrinkage (VS) and fiber length distribution were determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 40 publications
2
8
0
Order By: Relevance
“…Also, they can stop propagation of cracks in the restoration and increase modulus [21]. The differences in flexural properties presented in this study for bulk-fill composites and short fiber-reinforced composites are in accordance with previous research [11,22]. Differences in flexural properties between resin composites can be attributed not only to filler content but also to the type and size of the filler in the composition of the restorative material.…”
Section: Discussionsupporting
confidence: 89%
“…Also, they can stop propagation of cracks in the restoration and increase modulus [21]. The differences in flexural properties presented in this study for bulk-fill composites and short fiber-reinforced composites are in accordance with previous research [11,22]. Differences in flexural properties between resin composites can be attributed not only to filler content but also to the type and size of the filler in the composition of the restorative material.…”
Section: Discussionsupporting
confidence: 89%
“…After 24 hours of curing among other tested materials, SFRC yielded the highest Vickers hardness (61.4) at baseline measurements. In addition to the previous mentioned papers, many other laboratory studies have demonstrated the improved mechanical performance of SFRC, especially fracture toughness and flexural strength in comparison to the tested bulk‐fill or conventional PFC resins …”
Section: Resultsmentioning
confidence: 99%
“…Other practical factors such as the patient's diet and dental hygiene can also impact surface characteristics 48 . Empirically, a resin composite's hardness is commonly correlated with mechanical strength, rigidity and resistance to occlusal degradation in the oral cavity 49 . Structurally, the hardness of the resin materials is closely related to filler size, shape and fraction in the inorganic phase, generally increasing with filler content 50 .…”
Section: Discussionmentioning
confidence: 99%